Neutron Methods for Archaeology and Cultural Heritage - Kardjilov, Nikolay; Festa, Giulia (Neutron Scattering Applications and Techniques, 2017)
This book provides an extensive overview of the application of neutron characterization techniques in cultural heritage to a broad audience and will be of interest to both scientists and non-scientists in the field. Archaeologists, paleontologists, restaurateurs and conservators, historians and collectors will be fascinated by the wealth of information that can be obtained using neutron techniques, while material scientists and engineers will find details of the experimental techniques and materials properties that can be determined. Neutrons, due to their weak interactions with materials, provide a penetrating, but non-invasive probe of bulk properties. They allow the characterization of the composition and mechanical properties of materials, helping to answer questions related to the dating, the manufacturing process or the state of degradation of artefacts. They allow detailed interrogation of the internal structures of objects that may be otherwise hidden from view. The first section of the book is dedicated to stories describing spectacular discoveries brought about by the use of neutron techniques in a range of applications. The second section covers the experimental techniques in appropriate detail: basic principles, limitations and fields of application. .